Monitoring the elderly during the coronavirus pandemic: Experience report - Gonring Xavier, Fabiana; de Melo Batista, Karla; Maia Martins Sales, Carolina; Soares Nogueira, Rafael; Albina Ribeiro, Luiza (Guará Journal, 2024)
This article reports on the experience of developing a project to monitor 209 elderly individuals registered with the Open University for the Elderly. The project was led by nursing faculty and students at the Federal University of Espírito Santo and aimed to provide support, health monitoring, and guidance on COVID-19 prevention measures. Telephone calls lasting an average of 30 minutes were conducted from April to October 2020. Six forms were also administered to monitor health conditions, track vaccination status, preventative measures, and address social isolation. It was initially found that 89% reported being well, with reports related to changes in routine, loss of activities, and social interaction. It is important to highlight that there was a 7.7% increase in the use of new medications, primarily analgesics. Approximately 90% were familiar with the prevention measures, and there were no reports of clinical manifestations of COVID-19 during the intervention. The project provided security to the accompanied elderly and, to the students, experiences for the development of basic nursing care tools, in an intergenerational movement of exchange of knowledge, experiences and new learning, stimulating adjustment to the experienced context and action as citizens and future professionals.
Keywords: Elderly; Coronavirus; Pandemic